DECISION SUPPORT SYSTEM IN THE ADAPTIVE TEACHING RESOURCE IMPLEMENTATION. ANALYSIS OF USE - E. V. Kondratyonok; V. A. Kondratyonok (Системный анализ и прикладная информатика)
The results of the analysis of the need and intensity of control to the students at different levels of readiness in accordance with the theoretical model in the implementation of adaptive educational resource. It is proposed to use a factor driving the first impact at each stage of training, depending on the desired result indicator and opportunities of the teacher, the composition and content of training modules adaptive educational resource and budget allocation teacher training load.